Therapeutic Culture and Religion in America - Rakow, Katja (2013)
Much has been written about the psychologization of different spheres of contemporary American culture (education, industrial-military complex, health care, etc.) from different disciplinary perspectives. In this article, I will discuss the concept of therapeutic culture in relation to religion in America. The essay will trace contemporary therapeutic culture back to the mind cure movement and "New Thought" and its concept of the instrumental power of thoughts. A variety of 20th century developments that can be framed both as secular and as religious or spiritual, such as positive thinking, self-help, 12-step programs, New Age, and the so-called Prosperity Gospel, have predecessors in New Thought. Furthermore, the essay will survey early influential works on therapeutic culture in America. Philip Rieff's Triumph of the Therapeutic (1966), Christopher Lasch's The Culture of Narcissism (1979), and Eva S. Moskowitz's more recent study In Therapy We Trust (2001) are based on the idea that traditional Protestant religion has been eroded and replaced by the therapeutic ethos. These authors are concerned that America has traded its soul for its psyche and has swapped religion for therapy. In contrast, Eva Illouz' Saving the Modern Soul (2008) introduces a more comprehensive understanding of the therapeutic discourse as a new cultural matrix that permeates society as a whole. Moreover, a discussion of different historical studies on the interrelation of Protestant religious cultures and therapeutic ethos in the United States will demonstrate that it is not simply a relationship of replacement but one of intricate interconnection and entanglement. The works under discussion show that clinical pastoral education programs, Alcoholics Anonymous, and the Salvation Army adapted psychology and therapy to facilitate religious counseling, to foster outreach to homeless men, and to create spiritual engagement and fellowship among inebriates. As I explore the relationship between therapeutic culture and religion in America, I will point out central themes, possible shortcomings of approaches to the therapeutic so far, and desirable avenues for future research into the interplay of the therapeutic and religion.